A seismic behavior and numerical model of narrow paneled cross-laminated timber building. (15th January 2019) - Sato, Motoshi; Isoda, Hiroshi; Araki, Yasuhiro; Nakagawa, Takafumi; Kawai, Naohito; Miyake, Tatsuya
Highlights: This paper presents results of shaking table testing for full-scaled CLT building and a design procedure. This building system is suitable for midrise CLT building with high ductility produced through rocking. The structure was shown to behave well during severe strong motion as specified in the Japanese building standard law and to have survived the 1995 Kobe earthquake despite the occurrence of a compressive rupture in its shear wall as well as a support element against the vertical load. Element tests and connection tests for various types of shear wall were conducted to define a numerical model and its parameters, and a shaking table test was conducted to confirm the model and its parameters and to evaluate structural performance. A target Structure composed of narrow shear walls and high ductile tensile bolts was designed so as to satisfy the minimum requirement of Japanese building standard law. Story shear capacity calculated from a numerical model and element tests (such as connections) were safely evaluated; but to evaluate the capacity correctly, further research is required in the element and system levels. Though a variety of undetermined issues and challenges remains, the Building Standard Law and Notification for three different CLT construction systems was enforced in April 2016 to ensure the construction of safe CLT buildings. Abstract: A national research project to investigate proper structural design methods for cross-laminated timber (CLT) buildings has been initiated by a subsidiary of the Ministry of Land, Infrastructure, Transport and Tourism of Japan since 2011. In the final stage of the project, shaking table tests were conducted for CLT buildings designed according to a proposed structural design procedure which confirmed damage limit state, safety limit state, allowable stress, and ductile factors, etc. This paper presents results of shaking table testing for full-scaled CLT building and a design procedure. The three different systems examined are buildings composed of narrow panels, wide panels with an edge tensile connection, and wide panels with an edge tensile connection for each no-window shear part. The focus of this paper is the building of narrow panels. This building system is suitable for midrise CLT building with high ductility produced through rocking. The structure was shown to behave well during severe strong motion as specified in the Japanese building standard law and to have survived the 1995 Kobe earthquake despite the occurrence of a compressive rupture in shear walls which are support elements against the vertical load. Story shear capacity calculated from a numerical model and element tests (such as connections) were safely evaluated; but to evaluate the capacity correctly, further research is required in the element and system levels. Though a variety of undetermined issues and challenges remains, the Building Standard Law and Notification for three different CLT construction systems was enforced in April 2016 to ensure the construction of safe CLT buildings.